A Case of Benign Giant, Schwannoma and Review of literature (Pulse, 2014)
Though variety of benign and malignant tumors of peripheral nerve origin can occur in the mediastinum, benign schwannoma is the most common neurogenic tumor in the mediastinum Schwannoma is a non cancerous (benign) tumor that involves the Schwann cells in the protective covering of nerves, called the myelin sheath. Schwannoma is the common neurogenic tumor in the mediastinum. They are most often asymptomatic but sometimes accompanied by bloody pleural effusion. Herein, we report a case of giant, benign schwannoma presented with minimum symptoms of back pain and occasional chest pain. The case is reported here along with a literature review. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20350 Pulse Vol.6 January-December 2013 p.48-50